SOSIALISASI PERPAJAKAN PEMADANAN NIK MENJADI NPWP SERTA TATA CARA PELAPORAN SPT PPH ORANG PRIBADI DAN UMKM - Agustina Indriani; Radina Modjaningrat; Saminem Saminem; Sukardi Sukardi; Nur Syamsiah; Sitti Marwa Kharie (LPPM Universitas Bina Bangsa, 2023)
This community service (Pkm) is thanks to the agreement between the Tax Center Cooperation of Darma Persada University and the Directorate General of Taxes of the East Jakarta Regional Office. Where the goal is to socialize how to match NIK into NPWP and procedures for reporting Personal and MSME income tax returns. This activity is a collaboration of 2 campuses, namely Darma Persada University in East Jakarta and Morotai Pacific University located on Jl. Siswa Darame, South Morotai, Morotai Island Regency. Participants are open to all students and all employees at the two universities are also open to the public, which was previously published on social media both on the Instagram tax center of Unsada and also Unsada Official. Conducted online with zoom media with a lecture approach, and discussions on how to validate NIK into NPWP and also reporting Individual Taxpayer Tax Returns in various cases encountered by both taxpayers in the tax field